Scurrula atropurpurea increases nitric oxide and decreases malondialdehyde in hypertensive rats - Nour Athiroh AS; Erna Sulistyowati (Universa Medicina, 2013)
BACKGROUNDHypertension is the most prevalent chronic disease and has an impact on one billion people. Production of superoxide radicals and endothelial dysfunction are involved in hypertension. Scurrula atropurpurea (BL.) Dans. is a tea plant parasite. This study aimed to evaluate the role of Scurrula atropurpurea (BL.)Dans. on nitric oxide (NO) as a marker of endothelial dysfunction and malondialdehyde (MDA) as a marker of oxidative stress in hypertensive rats.METHODSThis study subjected rats to deoxycorticosterone acetate (DOCA)-induced hypertension. The experimental groups consisting of the control group and 3 hypertension groups receiving Scurulla  tropurpurea extract at a dosage of 50; 100; and 200 mg/KgBW. Scavenging activity of Scurrula atropurpurea (BL.) extract was analyzed by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The levels of arterial nitric oxide (NO) and pulmonary  malondialdehyde (MDA) were analyzed by spectrophotometry. ANOVA and a post hoc test were applied to find the difference of arterial NO and pulmonary MDA levels between groups.RESULTSThe level of arterial NO was significantly decreased in the hypertension groups as compared with the control group, while the level of pulmonary MDA was significantly increased (p<0.05). Scurulla atropurpurea significantly increases the NO level at a dosage of 200 mg/KgBW, compared with the hypertension groups (p<0.001). Scurulla atropurpurea significantly decreases pulmonary MDA level at a dosage of 100 and 200 mg/KgBW compared with the hypertension groups (p<0.05).CONCLUSIONScurulla atropurpurea extract increases arterial NO and decreases pulmonary MDA in hypertensive rats, thus playing an important role in endothelial dysfunction and oxidative stress.